THE EFFECT OF CONFUCIANISM TO THE MAIN CHARACTERS’ ATTITUDE TOWARDS THEIR FRIENDSHIP AND THEIR MARRIAGE IN SNOW FLOWER AND THE SECRET FAN BY LISA SEE - Sari, Anita; Maharini, May Triranto (CV. Pena Persada, 2020)
Most countries have culture to show their identity in the world. China is one of them which has exotic tradition from others since century years ago. One of the exotic traditions was known as footbinding. Furthermore, Chinese mostly believes Confucianism as a study in their life and conceives of every organization as a patriarchy. The goal of the study is to present the impact of Confucianism to the main characters, Snow Flower and Lily, towards their friendship and their marriage shown in the novel, Snow Flower and the Secret Fan. The doctrine of Confucius or Confucianism that they do when they were children has influenced their life, especially to their friendship and their marriage. The study also wants to find out their attitude and their marriage as the effect of Confucianism. Library research is used as the research method in this study. To answer the problem, the study explains about characters and setting, which are parts of elements of fictions. It also explains about friendship, marriage in China, and Confucianism itself. It can be concluded that Confucianism has an effect to the main characters’ attitude toward their friendship and their marriage. One of the main characters’ attitude has changed her friendship and got lucky in her marriage because of Confucianism.